1998
DOI: 10.1143/jpsj.67.3691
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of Superconductivity on the Anisotropic Triangular Lattice Hubbard Model: An Effective Model of κ-(BEDT-TTF) Salts

Abstract: We study the electronic states of the anisotropic triangular lattice Hubbard model at half filling, which is a simple effective model for the organic superconducting κ-BEDT-TTF compounds. We treat the effect of the Coulomb interaction by the fluctuation exchange (FLEX) method, and obtain the phase diagram of this model for various sets of parameters. It is shown that the d-wave superconductivity is realized in the wide region of the phase diagram, next to the antiferromagnetic states. The obtained phase diagra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
174
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 21 publications
13
174
1
Order By: Relevance
“…59,60) It has been shown that the superconducting critical temperature with a relevant order T c ∼ 100K is obtained by the FLEX approximation for High-T c cuprates. 61,62,63,64,65,66,67) The relevant results are also obtained for the organic superconductor κ-(BEDT-TTF) compounds 68,69,70) and for the ladder type compound Sr 14−x Ca x Cu 24 O 41 . 71) Moreover, the FLEX approximation is used to explain the anomalous properties resulting from the anti-ferromagnetic spin fluctuations, such as the Hall coefficient, 72, 73) the neutron resonance peak and the dip-hump structure in ARPES.…”
Section: §1 Introductionmentioning
confidence: 88%
“…59,60) It has been shown that the superconducting critical temperature with a relevant order T c ∼ 100K is obtained by the FLEX approximation for High-T c cuprates. 61,62,63,64,65,66,67) The relevant results are also obtained for the organic superconductor κ-(BEDT-TTF) compounds 68,69,70) and for the ladder type compound Sr 14−x Ca x Cu 24 O 41 . 71) Moreover, the FLEX approximation is used to explain the anomalous properties resulting from the anti-ferromagnetic spin fluctuations, such as the Hall coefficient, 72, 73) the neutron resonance peak and the dip-hump structure in ARPES.…”
Section: §1 Introductionmentioning
confidence: 88%
“…What is interesting though is that the proposed scenario can give a unified approach to SC in all organic CTS, irrespective of whether the insulating state proximate to SC is AFM 102 , CO 67,103 or VBS 82 . Recall that within existing mean field theories the AFM-to-SC transition is driven by spin fluctuations [13][14][15][16][17][18][19][20][21][22][23] , while the CO-to-SC transition is driven by charge fluctuations 65 . Even if we ignore that recent precise numerical calculations [25][26][27] have demonstrated the absence of SC within the proposed spin-fluctuation models in this context (thereby raising doubts also about mean-field theory of charge-fluctuation mediated superconductivity), different mechanisms of SC for structurally related materials with identical or nearidentical molecular components appear to be unrealistic.…”
Section: Consequence Of Stronger Frustration-paired Electron Liquid Amentioning
confidence: 99%
“…An extension of the RVB theory of dopant-induced SC in ρ = 1 is the proposal that frustration-induced SC occurs in the anisotropic triangular lattice within the simple Hubbard model even for ρ exactly 1, where a narrow superconducting phase is straddled on both sides by broader PM and AFM insulator phases [13][14][15][16][17][18][19][20][21][22][23] . It has been claimed that this transition explains the SC in the CTS [13][14][15][16][17][18][19][20][21][22][23][24] . Recent numerical work by us and others, however, have determined that SC is absent within the ρ = 1 triangular lattice Hubbard model [25][26][27] and the earlier results are artifacts of mean-field approximations.…”
mentioning
confidence: 99%
“…In analogy to these theories, mean-field and dynamic mean-field theories of κ-(ET) 2 X have proposed that SC also occurs within the exactly 1 2 -filled band Hubbard model on an anisotropic triangular lattice, for a range of Hubbard U and anisotropy [7][8][9][10][11][12][13][14][15][16] . A necessary condition for SC within any interacting electrons model however is that interactions must enhance superconducting pair-pair correlations relative to the noninteracting model.…”
Section: Introductionmentioning
confidence: 99%